2008
DOI: 10.1523/jneurosci.1465-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Function and Structure of the Right Inferior Frontal Cortex Predict Individual Differences in Response Inhibition: A Model-Based Approach

Abstract: The ability to suppress one's impulses and actions constitutes a fundamental mechanism of cognitive control, thought to be subserved by the right inferior frontal cortex (rIFC). The neural bases of more selective inhibitory control when selecting between two actions have thus far remained articulated with less precision. Selective inhibition can be explored in detail by extracting parameters from response time (RT) distributions as derived from performance in the Simon task. Individual differences in RT distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
247
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(278 citation statements)
references
References 40 publications
28
247
3
Order By: Relevance
“…They concluded that their data confirmed the role of inhibition in reducing semantic interference during picture naming. It should be noted, however, that other investigators (e.g., De Bruin et al, 2014;Forstmann et al, 2008;Verhoef et al, 2009) have associated inhibition with right inferior frontal cortex rather than with orbitomedial prefrontal cortex, as de Zubicaray et al did.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…They concluded that their data confirmed the role of inhibition in reducing semantic interference during picture naming. It should be noted, however, that other investigators (e.g., De Bruin et al, 2014;Forstmann et al, 2008;Verhoef et al, 2009) have associated inhibition with right inferior frontal cortex rather than with orbitomedial prefrontal cortex, as de Zubicaray et al did.…”
Section: Introductionmentioning
confidence: 82%
“…Commonly used tasks include the stop-signal task, where participants plan a response but must withhold it when a stop signal is presented on a minority of the trials (Logan and Cowan, 1984); the anti-saccade task, where participants see a flashing cue on either the left or right side of a screen and have to shift their attention and gaze quickly to the opposite side of the screen (Hallett, 1978); and the Eriksen flanker task, a choiceresponse task where participants choose a response to a central target stimulus that is flanked by non-target stimuli that are congruent or incongruent with the response to the target (Eriksen and Eriksen, 1974). Forstmann et al (2008) distinguished between nonselective response inhibition, http://dx.doi.org/10.1016/j.brainres.2014.07.009 0006-8993/& 2014 Elsevier B.V. All rights reserved. n which is engaged to stop any planned motor response, and selective response inhibition, which is recruited to selectively inhibit specific responses competing with a target response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced connectivity within the prefrontal cortex between the right DLPFC and the right iPFC in relation to increased deletion burden suggests deletions may be affecting local connectivity within the PFC and having a detrimental effect on the cognitive control network. The function of the right iPFC remains poorly understood, but appears to have a role in cognitive control, especially inhibition and reorienting [60][61][62]. Interestingly, functional connectivity between the right DLPFC region and a cluster predominantly in the right putamen was negatively correlated with total deletion burden.…”
Section: Iq -Neuroimaging Correlationsmentioning
confidence: 99%